THE EFFECTS OF GOLDEN SEA CUCUMBER EXTRACT ON TRIGLYCERIDE LEVELS OF HYPERLIPIDEMIC WISTAR RATS (Rattus norvegicus) - Angelina, Nadya (E-Jurnal Medika Udayana; Vol 11 No 5 (2022): E-Jurnal Medika Udayana, 2022)
Background : Hypertrigliseridemia was a condition where the triglyceride levels on the blood exceeds its normal level, in long term, it can cause serious complications such as a coronary artery disease which if not handled well, can cause a cardiovascular disease. Purpose : The aim of this study was to determine the golden sea cucumber ethanol 96% extract effect to triglyceride in hyperlipidemic rats. Method s : Design method in this study was true experiment. Male wistar rats, 150-250 g of weight, and aged 2-3 months. The rats were divided into 5 groups of 8, group KN (negative control), group KP (positive control), group PI (4,25mg golden cucumber extract), group PII (8,5mg golden cucumber extract), and group PIII (17mg golden cucumber extract). Measurement of triglyceride levels was twice, at eighth and eighteenth week. All groups were given standard food before treatment (week-0) and were given a high fat diet for 2 months and during treatment. Group KP was given simvastatin 1,2mg, group PI was given 4,25 golden cucumber extract, group PII was given 8,5mg golden cucumber extract, and group PIII was given 17mg golden cucumber extract for 2 weeks. The results were analyzed using Kruskal-Wallis. Results : The test results showed (p) = 0,034 which meant that the triglyceride has different meaning in each group. When compared, KN, KP, PI, PII, and PIII showed significant results. Conclusion : From the data analysis, it can be concluded that when given a golden sea cucumber extract, the triglyceride level in the hiperlipidemia rats can be lowered.